Does Dietary Calcium Source and Iron Interaction Affects Egg Laying performance, Quality and Yolk Iron Enrichment? - sharma, Amit; R. K. Gupta,; Daljeet kaur,; J. S. Hundal,; Gurpreet Singh,; R. V. Wagh, (Indian Journal of Animal Nutrition, 2022)
Present study was conducted to assess the interaction between dietary powdered and particulate   form of limestone as calcium source vis a vis graded levels of inorganic iron supplementation on egg production, quality and yolk iron enrichment. In a  3 X2  factorial experimental design,  a total of 72 BV-300 layer hens between 20-47 weeks of age were subjected to  total 6 treatments (with 3 replicates having 4 birds each) comprised of three dietary levels ( 50, 75 and 100 mg per Kg  feed) of iron and  two  levels of substitution ( 50 and 75 %) of fine limestone powder (LSP)  with  limestone grit (LSG). The source of calcium and iron interaction had significant effect on egg production and substitution of 75 % of LSP with LSG   along with increased iron supplementation significantly (p≤ 0.05) improved percent hen housed and hen day egg production and feed conversion ratio for egg mass production but   increasing LSG inclusion, only significantly (p≤ 0.05) improved egg shell thickness. Although egg yolk iron content was as per standards of iron fortified eggs but neither increasing LSG and iron supplementation improved egg yolk iron. It was concluded that   dietary substitution of LSP with LSG up to 75 % and 100 mg iron supplementation kg feed was an effective strategy to get optimum production of good quality iron enriched eggs during late laying phase.